The glacial history of Rocky Top cirque, southeast Fiordland, New Zealand - Moore, Emily (10798980) (2021)
Understanding natural climate variability is a fundamental goal of paleoclimate science. Temperate mountain glaciers are sensitive to climate variability, changing volume, and thus thickness and length, in response to changes in temperature and precipitation. Glaciers deposit moraines at their margins, which if well-preserved may provide evidence of glacier length fluctuations following glacial retreat. Therefore mountain glaciers can be used as proxies to investigate past climatic changes, offering the potential to reconstruct the timing and magnitude of natural climate variability and paleoclimate for the former glacier extent(s). This study applies methods of detailed geomorphological mapping and cosmogenic 10Be surface exposure dating to establish a high-precision moraine chronology and examine the timing and magnitude of glacier length changes at Rocky Top cirque. A quantitative reconstruction of paleoclimate for the identified former glacier extents was produced using an equilibrium-line altitude (ELA) reconstruction method and application of a temperature lapse rate. Findings show a clear pattern of glacial retreat at the end of the Last Glacial Maximum, with exposure ages from moraine boulders successfully constraining the timing of five distinct periods of glacier readvance or standstills. The most recent glacial event at Rocky Top cirque occurred between 17342 ± 172 yrs BP and during this period the ELA was depressed by 611 m. The second innermost moraine produced an indistinguishable age of 17196 ± 220 yrs BP and had an ELA depression of 616 m, indicating rapid glacial retreat. Progressively older moraines produced surface exposure ages of 18709 ± 237 and 19629 ± 308 yrs BP, with ELA depressions of 618 and 626 m respectively. The oldest moraine of 34608 ± 8437 yrs BP had insufficient geomorphic constraint to produce an ELA. Paleoclimate reconstruction results suggest that a best estimate of paleotemperature at the time of moraine formation (~19-17 ka) was between 3.2 ± 0.8 to 3.3 ± 0.8°C cooler than present-day. Net retreat of the former glacier is consistent with other similar moraine chronologies from the Southern Alps, which supports the regional trend and suggests that glaciers in the Southern Alps responded to common climatic forcings between ~19-17 ka.